Peningkatan Kualitas Hidup Penderita Diabetes melalui Senam Diabetes Di Klinik Tiara Medistra Tahun 2021 - Tani Astuti; Yusrial Tarihoran; Nurhaida Nurhaida; Mesrida Simarmata; Lisdayanti Simanjuntak; Srininta Srininta; Fitri Mayasari Panggabean (Pusat Riset dan Inovasi Nasional, 2023)
Diabetes is a carbohydrate metabolic disorder in the body caused by reduced insulin hormone from pancreatic beta cells as a result of the body's inability to respond to insulin. High glucose levels in the blood while lacking in cells can cause cells to become damaged, organ function is disrupted, resulting in injuries, kidney and retinal damage and neuropathy. Purpose: to improve the quality of life of diabetics by preventing diabetes complications Methods: Giving pre and post activity questionnaires, Providing material about diabetes and namely Demonstration of Diabetes Exercise and doing diabetes exercises once a week for 1 month at the Tiara Medistra Clinic. Results: For knowledge before giving the material the average score was 48.13 while after giving the material the average score was 68.75. For physical and psychological complaints: before the diabetes exercise the average score was 65.75 after the diabetes exercise the average score was 33.25. Conclusion: There was an increase in the quality of life of the participants after being given materials and demonstrations of diabetes exercise at the Tiara Medistra Clinic.